An Evaluation of ChatGPT in Education - Khan, Gulafshan Salam (International Journal on Orange Technologies, 2024)
ChatGPT is a powerful and versatile artificial intelligence (AI) language model, which has been widely used in the field of education. It has been developed to assist in text generation, translation, and data analysis tasks. The research is based on a systematic review of the literature and a SWOT analysis to assess the technology's strengths and weaknesses and identify opportunities and threats within the education sector. This study aims to determine the internal and external factors that impact ChatGPT’s success in education. This research will help shape the future of technology-assisted learning and inform policy decisions on using these technologies in educational settings.